Tubercular longitudinally extensive transverse myelitis (LETM): An enigma for primary care physicians - Kumar Abhishek Anand (Journal of Family Medicine and Primary Care, 2021)
Albeit, all forms of tuberculosis (TB) are endemic in India, spinal intramedullary TB and tubercular longitudinally extensive transverse myelitis (LETM) is deemed extremely rare. With recent advances in the field of neurology, autoimmune astrocytopathy (neuromyelitis optica spectrum disorders, NMOSD), myelin-oligodendrocyte glycoprotein associated encephalomyelitis (MOG-EM), metabolic myelopathy, connective tissue diseases and viral infections have gained considerable focus in the list of differentials of LETM whereas tubercular association is often forgotten. This report presents a rare case of acute transverse myelopathy which unveiled previously undiagnosed pulmonary tuberculosis in an adult rural Indian male. The patient responded well to anti-tubercular therapy and corticosteroids. Exact pathogenesis of LETM in TB remains elusive. Association of TB with MOG-EM has been one of the recent hot-cakes. However, an ill-defined immune-inflammatory response to the infectious agent is the likely cause of tubercular LETM. Hence, the primary care physicians who are the first medical contacts of acute LETM cases and in most cases due to diagnostic dilemma there is an unavoidable delay in accurate diagnosis and initiation of therapy. Primary care doctors should nurture a high index of suspicion to diagnose this potentially lifetime-debilitating yet absolutely treatable clinical condition i.e. tubercular LETM.